High Absolute Coronary Disease Risk among Turks: Involvement of Risk Factors Additional to Conventional Ones - Onat, Altan; Can, Guenay; Hergenc, Guelay; Kucukdurmaz, Zekeriya; Ugur, Murat; Yuksel, Husniye (KARGER, 2010)
Objectives: To confirm previous findings on excess absolute coronary heart disease (CHD) risk among Turks. Methods: The observed incident CHD risk of a representative population sample was compared with that anticipated by Framingham risk scores (FRS). At 7.4 years of follow-up of 3,027 participants free of CHD at baseline, risk estimation was contrasted in the 398 cases of newly developed fatal and nonfatal CHD. Results: CHD developed at a rate 2.2 times higher than the anticipated risk. In sex-specific quintiles of FRS, the 10-year incidence of CHD events in males in the 2 highest quintiles was 2 times the anticipated levels. In women, the 3 highest quintiles displayed an incidence 2.7 times the anticipated risk. Such individuals typically had abdominal obesity and evidence of dysfunctional apolipoprotein (apo) A-I. Men had high levels of non-high-density lipoprotein (HDL) cholesterol, total apoC-III, apoB and triglycerides. In Cox proportional hazard regression analyses, the 10-year probability of remaining free of CHD was low (81.1% in men, 84.2% in women). Women exhibited C-reactive protein as an independent predictor of CHD, lack of protection by HDL cholesterol and no conferred risk from current smoking. The observed excess CHD risk was primarily attributed to central obesity and related dysfunction of HDL, apoC-III and apoA-I. Conclusion: Dysfunction of protective serum proteins associated with metabolic syndrome impacts on CHD events, in addition to conventional risk factors. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Coronary disease risk prediction; Framingham risk score; Low-grade inflammation; Obesity; Risk factors; Turkish population; HIGH-DENSITY-LIPOPROTEIN; APOLIPOPROTEIN-A-I; METABOLIC SYNDROME; CARDIOVASCULAR RISK; HEART-DISEASE; CHOLESTEROL LEVELS; ARTERY-DISEASE; FRAMINGHAM; PREDICTION; POPULATION; Cardiovascular System & Cardiology